Let us see some examples and understand:

**Example 1:** Simplify the expression $\frac{(2\ -\ 7)}{5}$ $\times$ 2 + (8 - 2) $\times$ 3 and explain the steps.

**Solution:** The rules of BEDMAS will be used to simplify the given expression.

**1.** __Brackets:__ (2 - 7) = -5 and (8 - 2) = 6

The expression will be $\frac{5}{5}$ $\times$ 2 + 6 $\times$ 3

**2.** __Exponent:__ No exponent term is there.

**3.** __Division:__ $\frac{5}{5}$ = 1

The expression will be 1 $\times$ 2 + 6 $\times$ 3

**4.** __Multiplication:__ (1 $\times$ 2) = 2 and (6 $\times$ 3) = 18

The expression will be 2 + 18

**5.** __Addition:__ 2 + 18 = 20

**6.** As no more operations are there, the expression simplifies to 20.**Example 2:** Multiply the binomials (y - 11) and ($log_{x}$+ z).

**Solution:** Using the FOIL algorithm we can multiply these binomials.

**First:** Multiplying the first terms, y$\times$ $log_{x}$ = y$log_{x}$

**Outside:** Multiply the outer terms, y$\times$z = yz

**Inside:** Multiply the inner terms, -11$\times$ $log_{x}$ = -11 $log_{x}$

**Last:** Multiply the last terms, -11 $\times$ z = -11z

Adding all the terms we get, y$log_{x}$ + yz - 11 $log_{x}$ -11z.